2011
DOI: 10.4103/0259-1162.94761
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron, ramosetron, or palonosetron: Which is a better choice of antiemetic to prevent postoperative nausea and vomiting in patients undergoing laparoscopic cholecystectomy?

Abstract: Background:Postoperative nausea and vomiting (PONV) is a serious concern in patients undergoing laparoscopic cholecystectomy (LC), with an incidence of 46 to 72%. The purpose of this study was to compare the antiemetic efficacy of intravenous (iv) ondansetron 8 mg, ramosetron 0.3 mg, and palonosetron 0.075 mg for prophylaxis of PONV in high-risk patients undergoing LC.Materials and Methods:In this prospective, randomized, double-blinded study, 87 female patients, 18 to 70 years of age (ASA I and II) and underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…An additional study, found through a Google search, met the inclusion criteria and was included in this meta-analysis [14]. Thus, eight studies with a total of 695 patients were included in the final systematic review and meta-analysis [14–21] (Fig 1). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional study, found through a Google search, met the inclusion criteria and was included in this meta-analysis [14]. Thus, eight studies with a total of 695 patients were included in the final systematic review and meta-analysis [14–21] (Fig 1). …”
Section: Resultsmentioning
confidence: 99%
“…Because several studies defined the early and late phases differently, we combined the various periods of data collection with early and late periods. For the early phase, one study included data collected 0–1 hours [16] postoperatively, one study included data collected 2–6 hours [21] postoperatively, and one study included data collected upon arrival at post-anesthesia care units (PACU)[17]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations